2006
DOI: 10.1080/13614560600774313
|View full text |Cite
|
Sign up to set email alerts
|

Automated subject classification of textual Web pages, based on a controlled vocabulary: Challenges and recommendations

Abstract: The primary objective of this study was to identify and address problems of applying a controlled vocabulary in automated subject classification of textual Web pages, in the area of engineering. Web pages have special characteristics such as structural information, but are at the same time rather heterogeneous. The classification approach used comprises string-to-string matching between words in a term list extracted form the Ei (Engineering Information) thesaurus and classification scheme, and words in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…This is in compliance with previous results of the algorithm's performance, based on a pre-classified collection of research abstracts, where it was shown that certain classes have better performance than others (Golub et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…This is in compliance with previous results of the algorithm's performance, based on a pre-classified collection of research abstracts, where it was shown that certain classes have better performance than others (Golub et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…The fact that evaluations between the four tasks differed is in line with a previous study, where the algorithm's performance was tested on a pre-classified collection of research abstracts (Golub et al, 2007). The study showed that certain classes performed better than others.…”
Section: Automatically Assigned Classes As Judged By the User Study Psupporting
confidence: 70%
See 3 more Smart Citations